Effect of processing conditions on electromagnetic shielding and electrical resistivity of injection-molded polybutylene terephthalate compounds - Martins, Luís C. (2021)
This research introduces an analysis of the anisotropic electrical resistivity (ER) and its relation to the electromagnetic shielding effectiveness (EMSE) for two injection-molded carbon-fiber-reinforced polybutylene terephthalates (PBTs). The properties were measured for 2-mm thick injection moldings considering the effect of melt temperature, injection velocity, and flow distance. The results for one compound showed an EMSE in the range of 30–40 dB, while EMSE for a compound with lower filler content is in the range of 45–75 dB. A combination of higher temperature and higher velocity leads to an increase of EMSE for both compounds in the range of 3%–8.5%. However, the increase in flow path reduced the EMSE for both compounds up to 10%. A novel experimental apparatus was used to measure the anisotropic ER in the three directions, that is, parallel, perpendicular, and transversal to flow. It is evident that injection molding induced high anisotropy for both compound specimens, and, depending on the processing conditions, produced similar longitudinal resistivity (0.2–4 Ω.cm) but higher transversal resistivity (8–22 Ω.cm). ER properties were compared with EMSE, evidencing an inverse relation as expected. Furthermore, it was found that the longitudinal resistivity is the main contributor to the specimens shielding.